EKSPLORASI KONFLIK PSIKOLOGIS TOKOH DALAM SASTRA PASCA-REVOLUSI - M. Yusuf (Journal of Linguistics, Literature, Culture and History, 2025)
Post-revolutionary Indonesian literature (1945 and 1998) shifted from the collective heroism of the Generation of 45 to the individual inner conflict of the Generation of 66 due to the trauma of war, political disillusionment, and censorship of the New Order, as analyzed by Teeuw (1967) and Aprinus Salam (2012). This study aims to examine the form, representation, and function of psychological conflict among characters in postrevolutionary literary works to understand the reflection of historical trauma and social catharsis. A qualitative descriptive method with a literary psychology approach utilizes literature review of primary texts (Ziarah, Jalan Tak Ada Ujung, Laut Bercerita) and Lewin-Maslow's theory, similar to Frengki Umbu Gela (2017). The results show that identity, moral-ideological, emotional, and relational trauma are represented through inner monologues, fragmented plots, repressive settings, and metaphors, functioning as symbolic critique, collective healing, and humanization of characters. This research enriches literary studies with an Indonesian contextual psychoanalytic framework.